2016
DOI: 10.1073/pnas.1609811114
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy stability moderates the effect of status on stress and performance in humans

Abstract: High social status reduces stress responses in numerous species, but the stress-buffering effect of status may dissipate or even reverse during times of hierarchical instability. In an experimental test of this hypothesis, 118 participants (57.3% female) were randomly assigned to a high-or low-status position in a stable or unstable hierarchy and were then exposed to a social-evaluative stressor (a mock job interview). High status in a stable hierarchy buffered stress responses and improved interview performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 44 publications
(60 reference statements)
5
70
0
1
Order By: Relevance
“…Selecting the dominance behavioral strategy (hawk) may have caused cortisol concentrations to decrease, but selecting the deference behavioral strategy (dove) may have caused cortisol concentrations to increase. This pathway from behavior to cortisol changes is consistent with recent experimental evidence indicating that stable dominant positions buffer cortisol stress responses, whereas stable subordinate positions exacerbate cortisol stress responses (Knight and Mehta, 2017). This pathway is also consistent with evidence that acts of aggressive behavior can be rewarding and may reduce cortisol concentrations (Virgin and Sapolsky, 1997;Chester and DeWall, 2016).…”
Section: Cortisol Changes and Hawk-dove Decisionssupporting
confidence: 89%
“…Selecting the dominance behavioral strategy (hawk) may have caused cortisol concentrations to decrease, but selecting the deference behavioral strategy (dove) may have caused cortisol concentrations to increase. This pathway from behavior to cortisol changes is consistent with recent experimental evidence indicating that stable dominant positions buffer cortisol stress responses, whereas stable subordinate positions exacerbate cortisol stress responses (Knight and Mehta, 2017). This pathway is also consistent with evidence that acts of aggressive behavior can be rewarding and may reduce cortisol concentrations (Virgin and Sapolsky, 1997;Chester and DeWall, 2016).…”
Section: Cortisol Changes and Hawk-dove Decisionssupporting
confidence: 89%
“…More generally, animal and human studies indicate that potential loss of control produces stress in those at the top of the hierarchy (Knight & Mehta, 2017;Sapolsky & Share, 2004;Scheepers, 2009). Typically, when hierarchies are unstable, alpha males experience higher levels of stress than do alpha males in stable hierarchies (Gesquiere et al, 2011).…”
Section: Power Instabilitymentioning
confidence: 99%
“…Initially, ‘coupling’ was theorized to be observed primarily in adolescents who may need to maintain capacity to activate androgens even under stress (Ruttle et al, 2015; Susman et al, 2017), yet positive coupling has also been observed in adults (Bobadilla, Asberg, Johnson, & Shirtcliff, 2014, Harden et al, 2016). Marceau and colleagues (2014) examined coupling in response to three stressors and other research has examined multiple stress biomarkers (Bedgood, Boggiano, & Turan, 2014; Chatterton, Vogelsong, Hudgens, & 1997; Eatough et al, 2009; Knight & Mehta, 2017, Turan, Tackett, Lechtreck, & Browning, 2015). Yet to our knowledge, this is the first study to examine coupling of cortisol, testosterone, and DHEA during the TSST.…”
Section: Introductionmentioning
confidence: 99%